PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM KABUPATEN/KOTA, DAN PENGELUARAN PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI BALI - Olivia, Yolanda Sintaman; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p16, 2023)
The purpose of this study was to analyze the effect of economic growth, district/city minimum wages, and government spending on labor absorption in the province of Bali. The data analysis technique used is multiple linear regression analysis. Based on the analysis results indicate that the level of economic growth has a negative (not significant) effect on the level of employment in the Regency/City in the Province of Bali. The district/city minimum wage level has a positive (significant) effect on the district/city employment rate in Bali Province. The level of government expenditure has a positive (significant) effect on the level of absorption of Regency/City workers in the Province of Bali. Based on the research results, it can be suggested that the government can increase visits for both foreign and domestic tourists, thereby increasing the value of GRDP and the rate of economic growth. The government is also expected to provide employment programs so that the programs implemented can be right on target, with the right quality and on time as well as increasing labor productivity through education and labor training so as to create job opportunities for quality workers.